Research Competence of a Modern Teacher as a Factor in Improving the Quality of Education and Supporting Sustainable Development Goals (SDGs) - Liudmyla Hetmanenko; Liudmyla Khoruzha (ASEAN Journal of Educational Research and Technology, 2027)
This study examines teacher research competence as a factor in improving educational quality and supporting the Sustainable Development Goals (SDGs). Using theoretical analysis, survey data, and economic-mathematical modeling, the study clarifies the structure, conditions, and impact of research competence in modern teaching. Data from 10 secondary school teachers were collected through a questionnaire assessing professional competencies, temperament, motivation, stress resistance, and burnout. Communicative and methodological competencies were strongest, while research, managerial, digital, and inclusive competencies need further development. Research competence was positively related to intrinsic motivation and methodological competence. The study proposes a three-component model integrating research practice, professional communities, and motivational support to strengthen evidence-based teaching and sustainable educational improvement.